Using an Electronic Text-Matching Tool (Turnitin) to Detect Plagiarism in a New Zealand University - Goddard, R.; Rudzki, R. (Journal of University Teaching and Learning Practice, 2005)
This paper is concerned with reporting the experienceand findings of staff using a commercially-available textmatchingtool (Turnitin) to detect plagiarism in a universitysetting in New Zealand. The use of actual instances ofplagiarism revealed through Turnitin in a teachingdepartment is a departure from the more usual selfreportingmethodology used in many plagiarism researchpapers. The paper concludes by asking questions of theimplications for institutions, teaching staff and students.